Strategy To Improve Fine Motor Abilities Through Origami Paper Folding Activities In Children Of Group “B” At RA Masyitoh V Probolinggo - Kahar, Musdhalifah; Khadavi, M Jadid (PT Rizkarya Cendekia Pustaka, 2025)
ABSTRACT: This study aims to improve children's fine motor skills through origami paper folding activities in Group B children at RA Masyitoh V Karanganyar, Probolinggo. The approach used is qualitative with a case study method to explore in depth the process and impact of origami activities on children's fine motor development. The main focus of this study is on hand-eye coordination, accuracy, and muscle strength of children's fingers. Data collection techniques used include participatory observation, in-depth interviews with teachers and parents, and documentation of children's activities when folding paper. Data analysis was carried out using a qualitative descriptive method that includes data reduction, data presentation, and drawing conclusions. The results of the study showed that origami activities were able to significantly improve children's concentration, perseverance, and fine motor skills. Children showed an increase in their ability to grip, fold with precision, and regulate finger pressure when folding paper. So that origami paper folding activities can be used as an effective and fun method to stimulate the development of fine motor skills in early childhood, and can be applied routinely in learning at the Raudhatul Athfal level.